Simulated annealing approach for an overbooking appointment scheduling problem - Ab Rahmin, Nor Aliza; Nawawi @ Mohamed Nawawi, Athirah; Khairuddin, Nur Irdina Husna (Universiti Putra Malaysia, 2024)
No-shows are patients that do not show up for scheduled appointments or cancel at the last minute, preventing the health centre from filling the slot. Due to missed appointments, the health centre may lose time and money, and patient care may be compromised. In this study, we concentrate on patient no-show behaviour to reduce resource idle time, resource overtime, and patient waiting time. We aim to improve the overbooking appointment scheduling problem by applying the simulated annealing method after implementing the heuristics procedure. We also discover the effects of multiple patient assignments in the same slot, where we tend to find the greatest number of patients per slot that may be allocated to reduce costs. Our findings indicate that when using a large dataset of patients, simulated annealing performs slightly better than heuristics methods, and as a result, the maximum number that may be assigned to the same time slot is four.